Recycling leather waste: preparing and studying on the microstructure, mechanical, and rheological properties of leather waste/rubber composite - Santos, Renivaldo José dos [UNESP]; Agostini, Deuber Lincon da Silva [UNESP]; Cabrera, Flávio Camargo [UNESP]; Budemberg, Eduardo Roque [UNESP]; Job, Aldo Eloizo [UNESP] (Wiley Online Library, 2014)
Leather tanning processes cause environmental impactas a result of the generation of solid waste, wastewater,and release of gases. The improper disposal of suchwaste may promote the oxidation of chromium, forexample, changing it from chromium (III) to chromium(VI), in which becomes extremely toxic. In this study,composites were prepared from natural rubber (NR) withindustrial leather waste (Lw), varying the waste amountfrom 20 to 80 phr, with the aim of recycling leatherwaste. The microstructure, mechanical properties andrheological properties of composites were investigated.The results showed that Lwincreased tensile strengthand hardness, with good reproducibility, and uniformityof residuals distributed as fillers (miscible materials).These properties indicate that this composite materialcan be used as raw material for the manufacture ofshoes, bags, upholstery, etc.